Payments for ecosystem services in smallholder agriculture: lessons from the Hivos-IIED learning trajectory - Porras, Ina; Vorley, Bill; Amrein, Alexandra; Douma, Willy; Clemens, Harry (International Institute for Aerospace Survey and Earth Sciences, 2015)
This synthesis report presents highlights from six projects which are part of the joint Hivos-IIED PES Learning Trajectory Programme in five countries – Guatemala, Indonesia, Kenya, Nicaragua and Peru – that are exploring the use of carbon projects in smallholder farming. Through this research IIED and Hivos explore the feasibility of payments for ecosystem services (PES) as incentives to promote a shift to sustainable smallholder agriculture. Results from this research are published in the Payments for Ecosystem Services in Smallholder Agriculture series.